Edukasi Perilaku Cuci Tangan Pakai Sabun bagi Masyarakat Kelurahan Teluk dalam Menggunakan Teknologi Media Flipchart Berbasis Digital - Shalihah, Fatinatush; Yadiannur, Mitra; Ningsih, Rahma Pitria; Rahmah, Rahmah; Sulaiman, Sulaiman (Universitas Pahlawan Tuanku Tambusai, 2025)
Handwashing with Soap (CTPS) is a government priority program to promote healthy living awareness, as regulated in Ministry of Health Regulation No. 3 of 2014 and Law No. 36 of 2009. However, public awareness of CTPS in Indonesia remains relatively low. This community service activity was carried out in collaboration with the Family Hope Program (PPKH) facilitators in Banjarmasin, targeting beneficiary families (KPM) living in densely populated areas with a high risk of disease transmission. The main issue identified was the lack of knowledge and skills in practicing proper handwashing. The solution provided was health education on CTPS using digital flipchart media. The activity was held on July 29, 2025, with 32 participants. The results showed an improvement in participants’ understanding, skills, and awareness of the six proper handwashing steps according to health standards. This program effectively encouraged the habit of practicing clean and healthy living behaviors among social assistance beneficiaries.